2015
DOI: 10.1007/s00432-014-1902-1
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin is a novel prognostic biomarker in early-stage non-small cell lung cancer after surgical resection

Abstract: These results suggest that OPN is commonly expressed in NSCLC and may guide the evaluation of prognosis with NSCLC, especially for early-stage patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 23 publications
1
17
1
2
Order By: Relevance
“…Our results suggest that lung neoplasm patients have higher OPN serum levels, demonstrating that OPN serum levels may be important in the development of lung neoplasm. Previous findings have shown that there was a significant reverse correlation between OPN and overall and disease-free survival ( 20 ). Generally, OPN, an integrin-binding protein, is involved in numerous signaling pathways, such as cancer cell growth, adhesion, apoptosis, metastasis, proliferation, migration, invasion, and angiogenesis ( 7 , 35 , 36 ).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Our results suggest that lung neoplasm patients have higher OPN serum levels, demonstrating that OPN serum levels may be important in the development of lung neoplasm. Previous findings have shown that there was a significant reverse correlation between OPN and overall and disease-free survival ( 20 ). Generally, OPN, an integrin-binding protein, is involved in numerous signaling pathways, such as cancer cell growth, adhesion, apoptosis, metastasis, proliferation, migration, invasion, and angiogenesis ( 7 , 35 , 36 ).…”
Section: Discussionmentioning
confidence: 85%
“…Therefore, OPN may be considered a new diagnostic marker for predicting, detecting, and evaluating lung neoplasm. Additionally, OPN is a promising biomarker for lung neoplasm prediction, diagnosis, prognosis and even metastasis ( 5 , 20 , 21 ). However, other studies have presented inconsistent results ( 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…Three studies reported data on OPN expression and tumor TNM stage in NSCLC. 17 , 24 , 25 High OPN expression seemed to be associated with high tumor stage (III and IV) in two studies and low tumor stage in one study. Combined data from all the three studies showed a trend for a correlation between high OPN expression and high tumor TNM stage (III and IV) (OR =2.57, 95% CI 1.61–4.11, P <0.001) ( Figure 4 ) without any heterogeneity ( I 2 =0%, P =0.417).…”
Section: Resultsmentioning
confidence: 93%
“…Finally, a total of 13 studies 7 , 10 , 12 , 13 , 17 25 with 1,630 patients were included in our meta-analysis ( Figure 1 ). Four studies were performed in People’s Republic of China, 17 , 20 , 22 , 25 two in Japan, 12 , 13 two in America, 10 , 21 one in Norway, 19 one in England, 18 one in Italy, 7 one in Germany, 24 and one in Korea. 23 The sample size of each study varied from 25 to 244.…”
Section: Resultsmentioning
confidence: 99%
“…[ 6 ] One new area of research in early-stage NSCLC is identifying molecular markers tumor node metastasis (TNM) staging to completely evaluate the prognosis of NSCLC patients and to define novel strategies. [ 7 ] Numerous novel prognostic factors, such as osteopontin (OPN) and matrix metalloproteinase-7 (MMP-7), have been identified in NSCLC patients that may provide potential therapeutic targets for NSCLC, which are certainly warranted. [ 8 ]…”
Section: Introductionmentioning
confidence: 99%